Kudeta dalam Perspektif Hadis:Analisis Kontekstual dengan Pendekatan Ma’ānī Al-Ḥadīth - Zulfa, Nizam (Journal of Hadith Studies, 2021)
Coups are a political phenomenon that has occurred many times. Be it in the state leadership system, political parties, institutions and other organizations. Therefore, the phenomenon of a coup has the potential to always appear as long as there is a system of power. Seeing the phenomenon of coups which is part of politics, Islam as a kaffah religion , of course, has its own views, especially in this case the Qur'an and hadith. This assumption is the background for the researcher to conduct a study on the coup when viewed from the side of the hadith of the Prophet PBUH by departing from the hadith narrated by Abu Dawūd number 4248. This type of research is qualitative research and is descriptive-analytical. This research approach uses the theory of Ma’āni al-Ḥadīth as an analytical tool to interpret the hadith of the Prophet. In this case, the theory of Ma’āni al-Ḥadīth uses two methods, namely historical and hermeneutical. Data was collected through library research . From this study, the findings obtained are 1) historically, the hadith about the coup from the side of the study of sanad and matan is of authentic quality, so there is no doubt about the validity of the hadith. 2) The hadith about the coup (narrated by Abu Dawūd number 4248) entrusts obedience to the agreed leader as long as he does not deviate from the prevailing leadership norms. 3) The contextualization of the hadith about the coup in the Indonesian context is that the people are obliged to obey the President as a leader, because he is elected as a leader based on consensus through elections by all the people and as long as he is able to be a good leader. A coup in Indonesia could happen, but the chances are very small.